Sanksi Adat Perkawinan Poligami di Desa Pakraman Tenganan Pegringsingan, Desa Tenganan, Kecamatan Manggis, Kabupaten Karangasem - Wisuda, Pande Putu Toya; Puteri, Ni Nyoman; Ulio, Ulio (Institut Hindu Dharma Denpasar, 2020)
The Traditional Village of Tenganan Pegringsingan is a Bali Aga village whose conditions will be unique to its customs and culture. This can be seen in terms of building architecture, dress code , religious rituals and customary rules that are owned. Related to customary rules, Tenganan Pegringsingan village has had a rule that prohibits its citizens from conducting polygamy marriages. If there are societies who violate or engage in polygamy marriages, then they will be worn to customary law. The method used in this study is a descriptive qualitative method. In This research, data can be presented in the form of narrative text, words, expressions, opinions, ideas collected by researchers from several sources in accordance with data collection techniques. For the sanctions imposed on its citizens by the reason of: Maintaining Tradition, Maintaining Equality, and Maintaining Balance. The form of sanctions in the polygamy marriage namely; Sanctions Their Rights as Villagers Revoked, and Moral Sanctions. And the implication is Losing Rights as Villagers, and Not Getting Welfare.